2014
DOI: 10.1177/0258042x14535158
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Learning Act as a Mediator between the Relationship of Knowledge Management and Organizational Performance

Abstract: The study seeks to examine the correlation between organizational learning (OL), knowledge manage ment (KM) and organizational performance (OP) and to investigate the mediating role of OL between the relationship of KM and OP. The scope of the study was service and manufacturing sector organiza tions in India. The sample comprised of 118 respondents drawn from eight service and manufacturing sector organizations. The results revealed that OL is said to be partially mediating the relationship between KM and OP.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Additionally, present study findings revealed also that organizational performance has a significant and positive relationship with organizational learning which is according to the previous studies (Luxmi, 2014, Jaber & Caglar, 2017, Nafei, 2014, Mahmood et al, 2015, Ahmed et al, 2015. Finally, there is sound evidence that the mediator (OL) significantly mediates the relationship between predictor variable (KM) and Criterion variable (OP) in selected HEIs, which is in proportion to the findings of previous studies (Ramirez et al, 2011, Kou, 2011, Lin & Kuo, 2007, Rehman et al, 2015, Luxmi, 2014, Jaber & Cagler, 2017, Nefai, 2014, Imran et al, 2017, Abu Bakar & Yusof, 2016. As a result, it is important that the Higher Education Commission (HEC) and academic institutions (Universities) invest considerable investment in developing an organizational learning system that links knowledge management and organizational performance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, present study findings revealed also that organizational performance has a significant and positive relationship with organizational learning which is according to the previous studies (Luxmi, 2014, Jaber & Caglar, 2017, Nafei, 2014, Mahmood et al, 2015, Ahmed et al, 2015. Finally, there is sound evidence that the mediator (OL) significantly mediates the relationship between predictor variable (KM) and Criterion variable (OP) in selected HEIs, which is in proportion to the findings of previous studies (Ramirez et al, 2011, Kou, 2011, Lin & Kuo, 2007, Rehman et al, 2015, Luxmi, 2014, Jaber & Cagler, 2017, Nefai, 2014, Imran et al, 2017, Abu Bakar & Yusof, 2016. As a result, it is important that the Higher Education Commission (HEC) and academic institutions (Universities) invest considerable investment in developing an organizational learning system that links knowledge management and organizational performance.…”
Section: Discussionsupporting
confidence: 91%
“…By engaging the students, faculty, and industry, academic institutions can regularly improve their curriculum and assessment processes to produce market-based services and products that help develop the excellence of teaching and learning and meet quality assurance standards (Ngoc-Tan & Gregar, 2018). Furthermore, statistical evidence of the present findings indicates that organizational learning has a positive and significant relationship with knowledge management within academic institutions, which is in line with the previous results (Liao & Wu, 2009, Luxmi, 2014, Nafei, 2014, Sarand et al, 2015, Jaber & Caglar, 2017.…”
Section: Discussionsupporting
confidence: 90%
“…Superior performance is reliant on the "fit" quality between the strategic orientation of the organization and the resources that it possesses (Masa'deh et al, 2016). It is also reliant on the capacity of the organization in being good at innovation, in safeguarding its intangible knowledge assets, as well as in using these assets (Luxmi, 2014). Organizational performance is viewed as the organization's capacity in accessing and handling a variety of organizational resources for the attainment of its goals and objectives (Smriti and Das, 2018).…”
Section: Organizational Performancementioning
confidence: 99%
“…Luxmi (2014) defined firm performance as the actual outcomes produced by an organization compared to its planned outputs. Firm performance in this study refers to the combination of effectiveness and efficiency of individuals, groups, and organization at large (Tseng and Lee, 2014).…”
Section: Firm Performance (The Dependent Variable)mentioning
confidence: 99%